1980
DOI: 10.1136/gut.21.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis: an unrecognised entity.

Abstract: SUMMARY A patient is reported with chronic abdominal pain, diarrhoea, and associated radiological and endoscopic abnormalities of the sigmoid colon. Light and electron microscopic study of colorectal mucosa showed abnormal collagenous thickening of the subepithelial basement membrane. The authors felt that the clinical and morphological features justified a diagnosis of collagenous colitis. Review of the literature suggested that collagenous colitis was still an unrecognised entity. Lindstrom (1976) recorded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
2

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 13 publications
0
15
2
Order By: Relevance
“…7] when this comparison was made, the results showed that the thickness of the basement membrane was definitely abnormal in patients with col lagenous colitis. Furthermore, these results [2,7] would preclude the suggestion made by Whitehead [16] that collagenous colitis may be part of a normal spectrum. In a recent study [17] of a known case of collagenous colitis [2], we used an in direct immunofluorescence technique which showed an increased deposition of anticol lagen types I and III as well as antifibronectin antibodies at the site of the thickened collag enous deposit.…”
contrasting
confidence: 42%
See 2 more Smart Citations
“…7] when this comparison was made, the results showed that the thickness of the basement membrane was definitely abnormal in patients with col lagenous colitis. Furthermore, these results [2,7] would preclude the suggestion made by Whitehead [16] that collagenous colitis may be part of a normal spectrum. In a recent study [17] of a known case of collagenous colitis [2], we used an in direct immunofluorescence technique which showed an increased deposition of anticol lagen types I and III as well as antifibronectin antibodies at the site of the thickened collag enous deposit.…”
contrasting
confidence: 42%
“…Furthermore, these results [2,7] would preclude the suggestion made by Whitehead [16] that collagenous colitis may be part of a normal spectrum. In a recent study [17] of a known case of collagenous colitis [2], we used an in direct immunofluorescence technique which showed an increased deposition of anticol lagen types I and III as well as antifibronectin antibodies at the site of the thickened collag enous deposit. It is interesting to note that other immunofluorescence attempts have failed to identify immunoglobulins, comple ment, albumin or fibrinogen in the thickened basement membrane of collagenous colitis.…”
contrasting
confidence: 42%
See 1 more Smart Citation
“…Some investigators consider thickness >10 µm to be diagnostic, whereas others use >15 µm, and still others >30 µm [3,[5][6][7]11] . The SEBM thickness documented in cases of collagenous colitis in the English literature range from 11.5 to 60 µm [6,[13][14][15][16][17][18] . In a study of 564 patients conducted in 1982, the authors identified >10 µm in thickness as abnormal [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the thickness of the subepithelial collagenous band has generally attracted most attention [14], with less reference to the accompanying inflammatory cell infiltrate [3,5,6]. It is likely that the inflammatory component of this disease results in watery diarrhoea, just as it does in microscopic coli tis [15].…”
Section: Discussionmentioning
confidence: 99%